Synthesis, characterization and photocatalytic activity study of aluminium doped BiSbO4 microflakes. Issue 7 (1st April 2023) - Ajmal, Amna; El Sayed, Mohamed E.; Warsi, Muhammad Farooq; Murshed, Mohammad N.; Samir, Ahmed; El-Bahy, Zeinhom M.; Munir, Sana
Abstract: Metal oxides have an extraordinary ability to generate charge carriers with significant importance in environmental remediation. For the degradation of different dyes, a one-step hydrothermal method was adopted to synthesize Al-doped BiSbO4. While bismuth antimonate composite with reduced graphene oxide was synthesized by the simple ultra-sonication method. To investigate the structural confirmation, X-ray diffraction (XRD) was used. For studying morphology, scanning electron microscopy (SEM) was conducted. UV–Visible spectroscopy (UV) and Fourier transform infrared spectroscopy (FTIR) were used to observe the optical properties and vibrational modes of the as-synthesized BiSbO4 nanoparticles and doped Al–BiSbO4 . The above-mentioned studies verify the formation of nanoparticles of Al-doped BiSbO4 . The synthesized composite was used to degrade the organic dyes such as methylene blue and crystal violet. The degradation efficiency of doped, undoped and composite is studied and compared. The results indicate the extraordinary efficiency of BiSbO4 /rGO composite to doped and bare samples for the degradation of dyes. It is confirmed by the degradation of different dyes that the BiSbO4 /rGO composite shows the best catalytic efficiency.